Desamparo psíquico nos filhos de Dekasseguis no retorno ao Brasil - Resstel, Cizina Célia Fernandes Pereira [UNESP] (2014)
The dekasegi phenomena has been highlighted in Brazil due to the significant number of Japanese descendants who migrate to Japan in search of good jobs and financial improvement, then come back to Brazil after a long period or frequent coming and going trips. The overall purpose of this research elected as an object of investigation the experience of the dekasegi migrants, especially the sons of these migrants, Brazilian Japanese descendants who did performed the reverse way of migration in comparison with their grandparents and now are coming back to Brazil. The specific purpose of this research was to investigate how migrants’ children, who spent their early childhood or part of it in Japan, face the cultural adaptation process in Brazil, especially concerning to feelings and anxiety of abandonment. In order to that, psychoanalysis it was taken as a background theoretical reference and as a clinical method of scientific investigation based on interviews with parents and children. We noticed that in the cases’ reports a psychic abandonment discoursed in this research in dekaseguis’ children adaptation/readaptation process at the arrival at Brazil can be identified on children but also on dekaseguis parents themselves. These parents feel forgotten even before returning to Brazil. Therefore, there are uncountable difficulties for the dekasegui family at arriving at Brazil, being a bad feeling about the environment that were so familiar before as background, extending to a bad feeling about themselves. Besides, parents face their children’s cultural identity issue, hardly rooted at Japanese culture, what did not become so evident when they lived at Japan. Language will be the main index of deepest roots in children’s cultural identity, and the biggest challenge to be faced. As well, the age factor, foreign land standing period and scholarity degree these children have at the immigration ...